Surface and interface interplay on the oxidizing temperature of iron oxide and Au-iron oxide core-shell nanoparticles - Sarveena (2016)
This article presents the effect of oxidation temperature on shape anisotropy, phase purity and growth of core-shell heterostructures and consequently their effect on structure-property relationships. Iron oxide and Au-iron oxide nanocomposites were synthesized by a thermal decomposition method by passing pure oxygen at different temperatures (125-250 °C). The prepared nanoparticles were surface functionalized by organic molecules; the presence of the organic canopy prevented both direct particle contact as well as further oxidation, resulting in the stability of the nanoparticles. We have observed a systematic improvement in the core and shell shape through tuning the reaction time as well as the oxidizing temperatures. Spherical and spherical triangular shaped core-shell structures have been obtained at an optimum oxidation temperature of 125 °C and 150 °C for 30 minutes. However, further increase in the temperature as well as oxidation time results in core-shell structure amendment and results in fully grown core-shell heterostructures. As stability and ageing issues limit the use of nanoparticles in applications, to ensure the stability of the prepared iron oxide nanoparticles we performed XRD analysis after more than a year and they remained intact showing no ageing effect. Specific absorption rate values useful for magnetic fluid hyperthermia were obtained for two samples on the basis of detailed characterization using X-ray diffraction, high-resolution transmission electron microscopy, Mössbauer spectroscopy, and dc-magnetization experiments.